POR TRÁS DAS LENTES: A PERSPECTIVA DA ARTISTA EM A LINE MADE BY WALKING E EM COMO SER AS DUAS COISAS - Silva Ferreira, Joicy (Revista (Entre Parênteses), 2025)
By offering a new way of dealing with the present, photography becomes one of the best options for artists who are struggling in their lives. This is the case of Frankie and George, the protagonists of A Line Made by Walking and How to Be Both, respectively. It is through photography that they find themselves and new paths in their careers. Both the specificities of photography and its historical development are evoked in the narratives. Thus, the present paper focuses on the role of photography in Sara Baume’s and Ali Smith’s novels, observing how it contributes to the construction of each of the artist-protagonists.